Cosmic-ray production of tungsten isotopes in lunar samples and meteorites and its implications for Hf-W cosmochemistry - Leya, I; Wieler, R; Halliday, A (2000)
Excesses and deficiencies in 182W in meteorites and lunar samples relative to the terrestrial 182W atomic abundance have been assigned to the decay of 182Hf (t(1/2)=9 Ma) and have been used to date metal-silicate fractionation events in the early solar system. Because the effects are very small, production and burn-out of tungsten isotopes by cosmic ray interactions are a concern in such studies. Masarik [J. Masarik, Contribution of neutron-capture reactions to observed tungsten isotopic ratios, Earth Planet. Sci. Lett. 152(1997) 181-185] showed that neutron-capture reactions on tungsten isotopes can account at best for a minor part of the observed deficit of 182W in Toluca and other iron meteorites. On the other hand, in lunar samples and stony meteorites the production of 182W from 181Ta may become crucial. Here, we calculate this contribution as well as production and consumption of 182-186W by other neutron-induced reactions. The neutron fluence of each sample is estimated by its nominal cosmic-ray exposure age deduced from noble gas data. This approach overestimates the true cosmogenic W isotopic shifts for samples that might have been irradiated very close to the regolith surface. A quantitative estimate is often also hampered by a lack of Ta data. Despite these reservations, it appears that in many lunar samples neutron-capture on Ta has caused a large part of the observed 182W excess. On the other hand, in some samples, especially those with very low exposure ages, clearly only a minor or even negligible fraction of the 182W excess can be cosmogenic. Therefore, the conclusion, based on Hf-W model ages, that the Moon formed 50 Myr after the start of the solar system remains valid. Martian meteorites have lower Ta/W ratios and cosmic ray exposure ages than most lunar samples. Therefore, cosmogenic production has not significantly altered the W isotopic composition in Martian meteorites. Observed 182W excesses in Martian meteorites as well as the very large excesses in two eucrites are undoubtedly the result of early 182Hf decay. (C) 2000 Elsevier Science B.V. All rights reserved.